Effects of two Fluoride Mouthwashes on Surface Topography and Frictional Resistance of Orthodontic Wires - Eilnaz Ehrami; Alireza Omrani; Masood Feizbakhsh (Frontiers in Dentistry, 2022)
Objectives: We compared the effects of fluoride mouthwashes on surface topography of orthodontic wires, and static and kinetic frictional forces between stainless-steel (SS) orthodontic brackets and SS and nickel-titanium (NiTi) archwires.